Answer:
2x^2+4x-16
Step-by-step explanation:
The quadratic can be written as
f(x) = a(x-z1)(x-z2) where z1 and z2 are the roots
f(x) = a (x-2)(x- -4)
a is the leading coefficient
f(x) = 2(x-2)(x+4)
= 2(x^2 -2x+4x-8)
= 2(x^2 +2x-8)
= 2x^2 +4x-16
Answer:
1/3
Step-by-step explanation:
Each friend gets 1/3 of an apple
Step-by-step explanation:
60x + 3300 = 24000
60x = 24000 - 3300
60x = 20700
x = 20700 ÷ 60
x = 345
x ≤345
336 divided by 75 which equals 4.48
Answer:
I don't know nahakan zhuaksnzbu mkauzgbs kiuhsbs s kiuhs